eLearning Readiness of HEIs Students during Pandemic: Domain and Gender Perspectives - Kartiwi, Mira (2020)
Internet have gradually transformed how the teaching and learning activities con-ducted in Higher Education Institutions (HEIs), despite the slow uptake in developing countries. In 2020, the pandemic has triggered a rapid shift of paradigm, and necessitated prompt switch in teaching methods around the world. This significant change has not only affected the educators to rethink and assess the notion of teaching and learning, but also for the students. While many have gained adequate exposure to eLearning, the prompt switch to remote learning has triggered a new set of challenges. The result of this study shows that although majority of students express their readiness for remote teaching and learning, the sudden shift to online mode prompted different concerns after the trial session start-ed. Hence, the assessment of readiness may only offer partial view of eLearning conundrum. Evaluation of students experience during the trial of remote teaching period shows interesting the different perceptions on online teaching mode be-tween male and female students, and among domain of the study. This highlight potential support that education institutions may provide to ease the transitions process.